2022
DOI: 10.3389/fnut.2022.755514
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Squalene From Tea Leaves (Camellia sinensis) and Its Variations With Leaf Maturity and Tea Cultivar

Abstract: Squalene is a precursor of steroids with diverse bioactivities. Tea was previously found to contain squalene, but its variation between tea cultivars remains unknown. In this study, tea leaf squalene sample preparation was optimized and the squalene variation among 30 tea cultivars was investigated. It shows that squalene in the unsaponified tea leaf extracts was well separated on gas chromatography profile. Saponification led to a partial loss of squalene in tea leaf extract and so it is not an essential step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…The quantification of squalene content was conducted following the methodologies of Shen et al [45] and Rothblat et al [46], with minor adjustments. In brief, the hairy roots were subjected to overnight drying in an oven set at 60 • C. For the subsequent steps, 200 mg of the dried sample was employed.…”
Section: Determination Of Squalene Contentmentioning
confidence: 99%
“…The quantification of squalene content was conducted following the methodologies of Shen et al [45] and Rothblat et al [46], with minor adjustments. In brief, the hairy roots were subjected to overnight drying in an oven set at 60 • C. For the subsequent steps, 200 mg of the dried sample was employed.…”
Section: Determination Of Squalene Contentmentioning
confidence: 99%
“…However, the domesticated varieties that are sold as houseplants are mostly smaller than their natural ones. Large, leathery leaves on Croton nigritanus range in different sizes (Yue et al, 2022).. They can be linear or spherical in some cases, and can be of different sizes.…”
Section: Introductionmentioning
confidence: 99%
“…When grown inside, it hardly ever blooms, according to Wen et al, (2018), Squalene is a triterpene with molecular formula C30H50, in which there are six isoprene units. Squalene was first identified in shark liver extract, and later found in the other tissues of shark and vegetable oils such as olive oil (Yue et al, 2022). Due to the high market demand for squalene, investigation to find other sources of squalene is very essential (Ardhyni et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…seed. An extensive study encompassing 104 genotypes of 30 Amaranthus species revealed squalene concentrations ranging from 10.4 to 73.0 g/kg in amaranth oil [13].…”
Section: Introductionmentioning
confidence: 99%